Effects of biodiesel blends on lubricating oil degradation and piston assembly energy losses. (15th September 2016) - Gulzar, M.; Masjuki, H.H.; Varman, M.; Kalam, M.A.; Zulkifli, N.W.M.; Mufti, R.A.; Liaquat, A.M.; Zahid, Rehan; Arslan, A.
Abstract: Fuel is considered a major influencing parameter for engine oil condition during extended engine operation. Its effects on engine oil performance is required to be investigated with the implementation of the worldwide biodiesel mandate in various countries. This research monitored the influence of biodiesel on the condition of engine lube oil by long duration testing on three fuels: DF as the baseline; 20% palm biodiesel and 80% DF (PB20); and 20% jatropha biodiesel and 80% DF (JB20). The tests were carried out on a single-cylinder CI engine. Sump oil samples were collected at regular intervals during 200-h tests, after which the rheological, tribological, and chemical properties of the samples were investigated. Results showed that the B20 fuels decreased the viscosity and increased the acidity of the engine oil. Piston ring-cylinder and piston skirt-cylinder tests, in which a high-stroke reciprocating test rig was used, showed a slight increase in friction and wear losses near the intervals of oil draining for the B20 fuels. Chemical analysis by Fourier transform infrared spectroscopy and ASTM standard testing showed a decrease in soot loading but an increase in the fuel residue, corrosiveness, and oxidation of the engine oil samples for B20 fuelled engine tests. Highlights: Effect of diesel and biodiesel (PB20 and JB20) on engine oil degradation. Biodiesel blends helped to reduce the soot loading in used engine oil samples. Slight rise in friction and wear of piston assembly for biodiesel blends. High oxidation and corrosion was observed with biodiesel blends.